PROGRAM PEMBERDAYAAN DHUAFA UNTUK MEMBANTU MENINGKATKAN EKOOMI DAN MENGUATKAN LANGKAHNYA UNTUK MASA DEPAN SYAIFULLAH - Shofi Jamilatun Niswah; Muhammad Rizky Alfariz; Muhammad Rafi Wirdiyan; Mulkan Habibi (Media Resonansi Pengabdian Masyarakat, 2025)
Students from Universitas Muhammadiyah Jakarta initiated an empowerment program for Syaifullah’s family, a young man with physical limitations living with his elderly father and younger sibling. The loss of his mother a year ago worsened their economic struggles. To help, students organized a fundraising campaign through social media.The program followed four stages: assessing the family’s needs, raising funds, distributing aid transparently, and providing training in skills and financial management. The funds were used to start a small business selling chips.As a result, Syaifullah’s family received both financial and moral support for a more independent life. This program not only improved their economic situation but also served as an inspiration for future empowerment initiatives, encouraging students to be more socially aware and engaged in supporting underprivileged communities.Keywords: Empowerment, Fundraising, Skills, Entrepreneurship, Moral support